Towards accurate measurements of specific heat of solids by drop calorimetry up to 3000 °C. (1st December 2021) - Razouk, Refat; Beaumont, Olivier; Hameury, Jacques; Hay, Bruno
Highlights: Thermal diffusivity and specific heat measurements at high temperatures with a same set-up. Traceability of specific heat measurements via electrical calibration with a specific device. Uncertainty assessment of specific heat measurements by drop calorimetry at high temperature. In-situ electrical and temperature calibration of the setup. Abstract: The French National Metrology Institute LNE-LCM has modified a high temperature Laser Flash apparatus in order to perform the measurement of the specific heat of solids by drop calorimetry. A sample hanging on a thin wire held by a motorised gripper, is heated by the inductive furnace and dropped into a heat-flux Calvet calorimeter maintained at near ambient temperature. The calorimeter is equipped with an in-situ electrical calibration system in order to perform accurate and reliable measurements of energy directly traceable to the International System of Units (SI). The electrical calibration system has been designed for the calibration of the calorimeter by electrical substitution (Joule effect) and remains in-situ during the drop of the heated sample, keeping exactly the same experimental configuration during both steps of calibration and measurement. The metrological features (sensitivity, linearity) of the calorimeter have been evaluated by investigating the influence of the level of energy and dissipation time on the determination of the sensitivity factor of the heat-flux calorimeter. A calibration and measurement procedure was established in order to enable the measurement of the enthalpy increments of solids up to 2700 °C. The first results obtained for the determination of the specific heat of α-alumina (SRM-720), tungsten and graphite, as well as for the measurements of the enthalpy of fusion of pure copper are in good agreement with literature values and a relative uncertainty of 5% can be obtained.